Morfonologia limbii romàne. I. Paradigmatica. O abordare teoretică pe baza materialului verbal - Cychnerski, Tomasz (Wydawnictwo Naukowe UAM, 2001)
This paper is the first of a series o f articles devoted to the morphonology o f contemporary Romanian. Its aim is to introduce the main notions o f the morphonological paradigmatics, such as morphonological alternation, its types, functions and conditioning. The theoretical apparatus is illustrated with examples of Romanian verbal inflection.
Morphonology of Romanian, I. Paradigmatics. A theoretical approach, based on the verbal material.